The Relationship between Nutritional Status and the Occurrence of Dental Caries in Elementary School Children at Wonosaren State Elementary School - Reflioni, Silvi; Susanti, Widia; Handayani, Selfi; Wulandari, Agustina (Universitas Muhammadiyah Surakarta, 2024)
Pendahuluan: Masalah kesehatan gigi dan mulut di provinsi Jawa Tengah masih tinggi yaitu 73,4% pada anak kelompok usia 10-14 tahun dan menempati peringkat ke-22 provinsi di Indonesia. Status gizi, kebersihan rongga mulut, pola makan merupakan faktor-faktor yang dapat menyebabkan karies gigi pada anak. Beberapa penelitian melaporkan terdapat hubungan antara status gizi dengan karies gigi. Penelitian ini bertujuan untuk menggambarkan dan menganalisis hubungan status gizi dengan terjadinya karies gigi pada anak usia sekolah dasar di SD Negeri Wonosaren. Metode: Penelitian ini adalah studi penelitian analitik observasional dengan pendekatan cross-sectional. Penelitian ini dilaksanakan pada bulan Agustus-September 2023. Sampel dipilih secara stratified random sampling sebanyak 100 subjek penelitian. Status gizi diukur dengan teknik antropometri, yaitu menggunakan pengukuran tinggi dan berat badan. Pemeriksaan karies gigi dilakukan dengan cara melakukan inspeksi dan sondasi gigi. Data dianalisis dengan menggunakan Statistical Program for Social Science (SPSS) versi 25. Untuk mengetahui hubungan status gizi dengan terjadinya karies gigi dianalisis dengan uji korelasi pearson. Hasil dinyatakan signifikan apabila p<0.05. Hasil: Uji korelasi pearson menunjukkan tidak ada hubungan antara status gizi (IMT/U) dengan karies gigi (p=0.179). Simpulan: Tidak terdapat hubungan antara status gizi dengan terjadinya karies gigi pada anak usia sekolah dasar di SD Negeri Wonosaren. Introduction: Dental and oral health problems in Central Java province are still high, namely 73.4% of children aged 10-14 years, and are ranked 22nd province in Indonesia. Nutritional status, oral hygiene, and diet can cause dental caries in children. Several studies report a relationship between nutritional status and dental caries. This study aims to describe and analyze the relationship between nutritional status and the occurrence of dental caries in elementary school-aged children at Wonosaren State Elementary School. Method: This research is an observational analytical study with a cross-sectional approach. This research was carried out in August-September 2023. The sample was selected using stratified random sampling of 100 research subjects. Nutritional status was measured using the BMI/Age technique, obtained from anthropometric weight and height measurements. Weight is measured using a step scale, and height is measured using a microtome. A dental caries examination is carried out by inspection and dental condition. Data were analyzed using the Statistical Program for Social Science (SPSS) version 25. It was analyzed using the Pearson correlation test to determine the relationship between nutritional status and the occurrence of dental caries. Results are declared significant if p<0.05. Results: Pearson correlation test showed no relationship between nutritional status (BMI/U) and dental caries (p=0.179). Conclusion: There is no relationship between nutritional status and the occurrence of dental caries in elementary school-aged children at SD Negeri Wonosaren.